Tass mistma háit visã vu ma iveról hinguefó vea: memórias, sociabilidade e saberes localizados, o Clube do Lar da Associação Linha do Rio - Klatt, Luana Isabel (2022)
This study aims to present memories, forms of sociability, identities and how the farmers are organized, they, white women, who are part of the Clube do Lar da Associação Linha do Rio, in the municipality of Santo Cristo/RS, in the rural community of Linha do Rio. . It will address the importance of knowledge located in thinking and doing science, access to ICTs and the aging of part of the members of the collective. The Clube do Lar here can be understood as a group of women farmers who meet every month to carry out an activity, which is assisted by Emater/RS-Ascar. The research was developed between the years 2020 to 2022, period of the Covid-19 pandemic, through an ethnography. For the research, participant observation was carried out online and in person with the group, in addition to conducting interviews with the founding members, members and former members of Emater/RS-Ascar, members of the Linha do Rio Association, and applying a questionnaire with the Club. It was observed that, over the years, the group developed a strong social importance at local level. In addition to the name “Clube do Lar”, women do not return to carrying out activities related to the home environment. When remembering its constitution, as well as the contributions and difficulties they had over the years of participation, they highlighted how integrating it reflects on their learning process, friendships, leisure, a symbolic extra income, encouragement and social participation. The period of the pandemic made the search for connection through ICTs and digital media between them, their daughter(s) and their family increase. As a consequence, learning and new uses of the body and on themselves, in the use of appliances, especially those over 60 years old. The group is not only important in their daily lives, but also enables the creation of bonds and networks with other women and social groups.